Metachronous Colon Metastasis to the Thyroid: A Case Report and Literature Review - Froylich, Dvir (Hindawi Publishing Corporation, 2013)
The thyroid gland is a known site for metastatic tumors from various primary sites. Thyroid metastases are not an exceptional finding at autopsy, and they are encountered in 2% to 9% of the patients with malignant neoplasm. The most frequent tumors to metastasize are breast, lung, melanoma, and kidney carcinomas. Despite the fact that it is one of the largest vascular organs in the body, clinical and surgical cases have given an incidence of 3% of secondary malignances of this organ. Metastatic colon carcinoma to the thyroid gland has been reported, and it is not as rare as one might think. We present a very unique case of colon carcinoma metastasis to the right thyroid lobe and lung five years after colon resection, with reoccurrence two years later in the contralateral thyroid lobe. The literature regarding colon cancer metastasizing to the thyroid gland was reviewed with an attempt to disclose features of this presentation regarding patient's prognosis.